2022
DOI: 10.1111/hae.14623
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 and SOX9 expression in haemophilic cartilage: In vitro studies of the effects of iron

Abstract: Introduction Clarifying the links between iron and FGF23, SOX9 expression in chondrocytes would be helpful for comprehending articular cartilage degradation pathogenesis in blood‐induced arthritis and exploring new protective methods. Aim The purpose of this study was to determine iron regulation of fibroblast growth factor 23 (FGF23) and SRY‐box 9 (SOX9) in human chondrocytes, an area which is unexplored in blood‐induced arthritis cartilage degradation pathogenesis. Methods Expression of FGF23, SOX9, MMP13 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…9 These inflammatory changes contribute to cartilage damage through the production of tissue-destroying enzymes and cytokines 10 leading to joint destruction. A recent study by Zheng et al 11 has shown how iron is involved in cartilage injury through regulation of FGF23 and SOX9 expression in chondrocytes in patients with hemophilia who have developed hemarthrosis. A high level of COL-18N has been noted in patients with hemophilia A 12 , which could be used as a potential marker to monitor the development of arthropathy, making it possible to adapt the best treatment to prevent further joint damage.…”
Section: Hemophilia Overview and Clinical Manifestationsmentioning
confidence: 99%
“…9 These inflammatory changes contribute to cartilage damage through the production of tissue-destroying enzymes and cytokines 10 leading to joint destruction. A recent study by Zheng et al 11 has shown how iron is involved in cartilage injury through regulation of FGF23 and SOX9 expression in chondrocytes in patients with hemophilia who have developed hemarthrosis. A high level of COL-18N has been noted in patients with hemophilia A 12 , which could be used as a potential marker to monitor the development of arthropathy, making it possible to adapt the best treatment to prevent further joint damage.…”
Section: Hemophilia Overview and Clinical Manifestationsmentioning
confidence: 99%
“…Moreover, iron catalyzes the conversion of hydrogen peroxide, produced by activated chondrocytes, into hydroxyl radicals, leading to chondrocyte apoptosis [12]. Iron affects fibroblast growth factor 23 and SRY-box 9 expression, causing cartilage degeneration in HA [18]. Also, subchondral bleeding is suggested to contribute to HA development by affecting subchondral bone health and probably inducing subchondral cyst formation [19].…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory changes contribute to cartilage damage, through the production of enzymes and cytokines that destroy the tissue, leading to joint destruction. 6 A recent study 7 has shown how iron is involved in cartilage injury through the regulation of the expression of FGF23 and SOX9 in chondrocytes in patients with hemophilia who have developed hemarthrosis. A high level of COL-18N has been observed in patients with hemophilia A, and it can be used as a potential marker to monitor the development of arthropathy, allowing the best treatment to be adapted to prevent further joint damage.…”
mentioning
confidence: 99%